1967
DOI: 10.1128/aem.15.5.1031-1037.1967
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Microorganisms by Electrohydraulic Shock1

Abstract: The electrohydraulic shock treatment of microorganisms was accomplished by discharging high-voltage electricity (8 to 15 kv) across an electrode gap below the surface of aqueous suspensions of the microorganisms. This treatment was effective in destroying Escherichia coli, Streptococcus faecalis, vegetative cells and spores of Bacillus subtilis, and bacteriophage specific for S. cremoris ML1. The presence of added protein in bacterial suspensions resulted in reduced bactericidal action. Water subjected to elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 11 publications
(9 reference statements)
3
15
0
Order By: Relevance
“…The present study showed that similar inactivation of native biota in whole raw milk can be achieved by H ⁄ PEF compared to conventional pasteurization, but the H ⁄ PEF hurdle approach proved to be slightly more effective in UHT milk. These findings are in agreement with the results of other researchers who suggested that the apparently greater stability of micro-organisms in raw vs UHT milk could be due to the altered physicochemical properties in the latter, as well as the presence of more fat and proteins (Gilliland and Speck 1967;Martín et al 1996). However, a study by Picart et al (2002) carried out with dairy cream did not confirm the protective effect of higher fat content towards micro-organisms exposed to PEF, which might indicate that there could be an 'optimal' fat level below that of cream providing maximum protection to the micro-organism.…”
Section: Storage Time (Days)supporting
confidence: 93%
“…The present study showed that similar inactivation of native biota in whole raw milk can be achieved by H ⁄ PEF compared to conventional pasteurization, but the H ⁄ PEF hurdle approach proved to be slightly more effective in UHT milk. These findings are in agreement with the results of other researchers who suggested that the apparently greater stability of micro-organisms in raw vs UHT milk could be due to the altered physicochemical properties in the latter, as well as the presence of more fat and proteins (Gilliland and Speck 1967;Martín et al 1996). However, a study by Picart et al (2002) carried out with dairy cream did not confirm the protective effect of higher fat content towards micro-organisms exposed to PEF, which might indicate that there could be an 'optimal' fat level below that of cream providing maximum protection to the micro-organism.…”
Section: Storage Time (Days)supporting
confidence: 93%
“…(1992) It is more difficult to reduce the number of microorganisms present in skim milk than in buffer solutions and model foods because the composition of skim milk is very complex (i.e., high protein content 33-40 g/L) (Goff and Hill 1993). These substances diminish the lethal effect of PEF in microorganisms by absorbing free radicals and ions which are active in the cell breakdown (Allen and Soyke 1966;Gilliland and Speck 1967a). Moreover, the inactivation of bacteria by PEF is a function of solution resistivity, which is inversely proportional to ionic strength.…”
Section: Treatment In a Static Chamber Systemmentioning
confidence: 99%
“…On the other hand, the presence of protein in the saline solution reduced the effectiveness of treatment and increased energy was required for complete sterilization. Proteins diminish the effect because they may absorb the active radicals and ions resulting from the discharges (Allen and Soike 1966;Gilliland and Speck 1967a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence of proteins and fats in liquid egg (Table 6), both important nutrients for microbial growth (Banwart 1989), add some constraints to the effectiveness of the PEF treatment. Fats exhibit a protective role for microorganisms and proteins diminish the effectiveness of PEF treatment because they may absorb the active radicals and ions resulting from the discharges (Allen and Soike 1966;Gilliland and Speck 1967).…”
Section: Fig 5 E Cow In Liquid Egg After Pef Treatment At 26 Kv/cmmentioning
confidence: 99%